METODE PEMBELAJARAN ENTREPRENEURSHIP UNTUK GURU SMK DI KABUPATEN LAMONGAN - Endang Sudarsih; Muchammad Nurif (Jurnal Sosial Humaniora, 2025)
This study is about a training of learning method for teachers, especially who teaches the subject of entrepreneurship in Senior High School. The target of the study is Vocational High School teachers in Lamongan. Some crucial problems that are faced by the most of educational institution are teachers’ low ability in finding references for students’ problem solutions. Their leakage of creativity and innovation will cause a lower level of students’ readiness to enter job fields after graduation. The goal of the study is to increase human resource quality in mastering learning methods that possible to be applied in entrepreneurship teaching-learning activities. By using an appropriate method, it is expected that it will improve teachers’ ability in finding references, developing creativity and innovations. Therefore, teachers enjoy teaching entrepreneurship subject with better spirits and students’ entrepreneurship spirit will also developed earlier.